The role of green human resource management and green innovation in enhancing environmental performance - Mentari Clara Dewanti; Daisy Marthina Rosyanti; Fani Khoirotunnisa (Journal of Innovation in Business and Economics, 2025)
This study explores the impact of Green Human Resource Management (GHRM) and Green Innovation on environmental performance within the hospitality industry, with a particular focus on the moderating roles of Green Creativity and Green Transformational Leadership (GTL). The research sample comprises 85 hospitality employees from East Java, selected through purposive sampling. Data collection was conducted via both online and offline questionnaires, and the analysis was performed using SmartPLS 4. Findings indicate that the success of environmentally friendly practices in the hospitality sector depends significantly on employees’ contributions through Green Innovation and Green Creativity. Consequently, it is crucial for organizational leaders to cultivate a supportive work environment by implementing HR practices aligned with sustainability objectives, thereby fostering higher employee engagement in green initiatives.